NATIONAL EDUCATION POLICY 2020: OPPORTUNITIES AND IMPLEMENTATION CHALLENGES AT GROUND LEVEL - PREETINDER GHAI (IJRDO- Journal of Educational Research, 2025)
The National Education Policy (NEP) 2020 marks a significant milestone in the evolution of the Indian education system, aiming to revamp the curriculum, pedagogy, governance, and assessment mechanisms across all stages of education. This paper explores the core opportunities the policy offers, especially at the school level, while critically analyzing the challenges encountered during its implementation at the grassroots. Drawing from field experience in a government school in Punjab, the paper highlights the ground realities, infrastructural limitations, teacher preparedness, and socio-economic disparities that affect the translation of NEP into practice. The article suggests actionable strategies to bridge policy and practice for equitable and quality education.